The malleable character of brokerage and crime control: a study of policing, security and network entrepreneurialism on Melbourne's waterfront - Brewer, Russell (Policing and society, 2017)
This article investigates the convergence of public and private security actors at the Port of Melbourne, and using social network analysis, maps the extent to which these actors actively mobilise network connections to control crime. The findings reveal a network structure characterised by a distinct separation of power amongst nodes that, as a consequence, obstruct the flow of network resources. Of particular interest to this article, is the capacity of actors to overcome structural barriers and mobilise connections across the entire network. This is achieved only through the prodigious efforts of several public, as well as private, actors who serve as ‘brokers’ and are positioned to bridge network barriers and modulate the flow of network resources. The most salient finding in this article is the scope of brokerage activities undertaken by private actors - and the extent they have been ‘entrepreneurial’ in terms of elevating their structural positioning, and targeting networking opportunities. In particular, it flags an important paradigm shift away from a state-centric literature that almost exclusively conceives brokerage as a function undertaken by public policing agencies. Rather, it illustrates that such positions are far more malleable than previously conceived, and that given the right circumstances, private interests can, and do, ascend to become dominant brokers of crime control. Accordingly, this article argues that the concept of brokerage offers important new insights into how security is delivered, and should be incorporated into wider scholarly debates of plural policing and the governance of security.